Evaluation of neurapheresis therapy in vitro: a novel approach for the treatment of leptomeningeal metastases. Issue 1 (18th April 2020) - Ejikeme, Tiffany; de Castro, George C; Ripple, Katelyn; Chen, Yutong; Giamberardino, Charles; Bartuska, Andrew; Smilnak, Gordon; Marius, Choiselle; Boua, Jane-Valeriane; Chongsathidkiet, Pakawat; Hodges, Sarah; Pagadala, Promila; et al.
Abstract: Background: Leptomeningeal metastases (LM), late-stage cancer when malignant cells migrate to the subarachnoid space (SAS), have an extremely poor prognosis. Current treatment regimens fall short in effectively reducing SAS tumor burden. Neurapheresis therapy is a novel approach employing filtration and enhanced circulation of the cerebrospinal fluid (CSF). Here, we examine the in vitro use of neurapheresis therapy as a novel, adjunctive treatment option for LM by filtering cells and augmenting the distribution of drugs that may have the potential to enhance the current clinical approach. Methods: Clinically relevant concentrations of VX2 carcinoma cells were suspended in artificial CSF. The neurapheresis system's ability to clear VX2 carcinoma cells was tested with and without the chemotherapeutic presence (methotrexate [MTX]). The VX2 cell concentration following each filtration cycle and the number of cycles required to reach the limit of detection were calculated. The ability of neurapheresis therapy to circulate, distribute, and maintain therapeutic levels of MTX was assessed using a cranial–spinal model of the SAS. The distribution of a 6 mg dose was monitored for 48 h. An MTX-specific ELISA measured drug concentration at ventricular, cervical, and lumbar sites in the model over time. Results: In vitro filtration of VX2 cancer cells with neurapheresis therapy alone resulted in a 2.3-log reduction in cancer cell concentration in 7.5 h and a 2.4-log reduction in live-cancer cell concentration in 7.5 h when used with MTX. Cranial–spinal model experiments demonstrated the ability of neurapheresis therapy to enhance the circulation of MTX in CSF along the neuraxis. Conclusion: Neurapheresis has the potential to act as an adjunct therapy for LM patients and significantly improve the standard of care.